PENGELOLAAN PEMBELAJARAN APLIKASI KOMPUTER AKUNTANSI (MYOB AKUNTANSI) SISWA KELAS XII AKUNTANSI DI SMK MUHAMMADIYAH 2 NGAWI - Handayani, Nora; Suyatmini, Suyatmini; rohmah, Wafrotur (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2015)
Purspose of the study was to determine : (1) Describe the learningplan on applying MYOB version 17, (2) Describe theimplementation of learning to apply MYOB version 17, (3) Describethe evaluation of learning apply MYOB accounting computerversion 17 on accounting class XII students in SMKMuhammadiyah 2 Ngawi.This research is a qualitative descriptive study, the object of study is accountingclass XII in SMK Muhammadiyah 2 Ngawi. Data collection techniques used arein-depth interviews with a number of informants, observation and documentation.Techniques of data analysis in this study using the interactive model of Milles andHuberman. Test validity of the data in this study through triangulation techniques,sources and triangulation time.The results of research conducted at SMK Muhammadiyah 2 Ngawi shows that :(1) Learning begins with the preparation of teachers of in making teaching devicethat consists of several learning planning document accounting computerapplication owned by teachers, education calender, the annual program, thesemester program, syllabus development, lesson plans enrichment and remedialprogram. (2) Implementation of learning accounting computer applicationsimplemented in a computer laboratorium and claasroom space with time of 8hour everyweek of face to face learning every class. CTL-based learning methodperformed by the teacher is lecturing, discussion and assignment through directpractice of manvally then applied to computer. Media practice learning iscomputer with application software MYOB version 17 and Microsoft power pointused when presenting material to students. Infrastructure in the implementation oflearning is still lacking, resulting in students can not focus in practice. (3)Evaluation of learning is done in the form of formative and summative, materialarranged in the form of essay and about the practice of manual. Assessmentpractices applied to computer based on the achievement of competencies derivedfrom components valve of weight multiplied by a score components remedialconducted for students who has not reached the KKM.